Encountering Muslim ‘Others’: Indonesians in the Muslim Diaspora of London - Wardana, Amika (Komunitas, 2014)
The article investigates the social relations between Indonesian immigrants and the multicultural Muslim community in London by examining the applicability of the Ummah concept, in the context of the diaspora. The Muslim diaspora, though their similarity of faith, has always contained internal diversity and fragmentation. Likewise, different religious trajectories of Muslim immigrants as illustrated by Indonesians in London have been identified to shape different understandings of unity and diversity of Muslims, which forge different forms of social relation with fellow Muslim immigrants in the city. The traditionalist London Indonesians have trivialized the unity of Muslim in diaspora through daily encounters yet maintained inevitable different ethnic affinities and religious-sectarian affiliations as a wall dividing them altogether. The revivalist Indonesians have construed the diasporic unity of Muslims as an idealized-normative concept that should be realized socially, culturally and politically by suppressing internal ethnic, national and religious-sectarian fragmentations. While the secularist Indonesians have shown an apathetic position to the implausibility of the diasporic unity of Muslims due to its irreconcilable perceived internal diversities and divisions.Artikel ini menelaah pola relasi sosial antara imigran Indonesia dengan masyarakat Muslim multikultural di London dengan menguji kesesuaian konsep kesatuan Ummat Islam dalam konteks diaspora. Meskipun memiliki persamaan iman, diaspora Muslim selalu terbangun dalam perbedaan internal dan perpecahan. Demikian pula dengan arah perkembangan religiusitas imigran Muslim yang beraneka-ragam termasuk yang berasal dari Indonesia yang pada akhirnya membentuk beberapa pola relasi sosial dengan komunitas Muslim lainnya di kota ini. Kelompok Muslim Indonesia tradisional menganggap biasa konsep kesatuan Ummat Islam dalam perjumpaan sehari-hari dengan komunitas Muslim lainnya sehingga tetap menjaga jarak berdasarkan perbedaan etnis dan afiliasi tradisi keagamaannya. Kelompok Muslim Indonesia revivalist memahami kesatuan Ummat sebagai konsep ideal yang perlu direalisasikan dalam kehidupan sosial, budaya dan politik sekaligus mengubur potensi perpecahan karena perbedaan etnis dan tradisi keagamaan. Sebaliknya, kelompok imigran Indonesia sekuler menunjukkan sikap apatis terhadap kesatuan Ummat karena adanya perbedaan dan perpecahan internal Ummat Islam yang tidak mungkin didamaikan.